PILIHAN KONSUMSI WAKTU SEKARANG DAN AKAN DATANG RUMAH TANGGA PETANI CENGKEH DI DESA HARUKU MALUKU TENGAH - Sabthu, Andre (Fakultas Ilmu Sosial dan Ilmu Politik, 2023)
This research aims to analyze the consumption behavior of clove farming households as well as the economic variables that influence savings from the harvest of dried clove commodities by farming households. Consumption in this research is the clove harvest that is sold and the results for consumption and savings in this research are abstracted as postponed consumption. To analyze the relationships and choices made by farming households in research using an intertemporal model. The main variables in this research are the amount of clove savings, the commodity price of cloves at harvest, the price of cloves in the future, clove income at harvest time, estimated future clove income, future consumption. This research uses primary data through questionnaires and in-depth interviews. The sample was taken based on purposive random sampling of 96 farmers who owned clove plantation land in Haruku Village. To analyze the magnitude of the influence of the independent variable on the dependent variable, cross-section regression was used using the Eviews tool. The research results show that the price variables at harvest, the estimated price of cloves in the future, and future consumption affect the clove savings of farmer households.